2020
DOI: 10.1007/s10147-020-01726-6
|View full text |Cite
|
Sign up to set email alerts
|

Central statistical monitoring of investigator-led clinical trials in oncology

Abstract: Investigator-led clinical trials are pragmatic trials that aim to investigate the benefits and harms of treatments in routine clinical practice. These much-needed trials represent the majority of all trials currently conducted. They are however threatened by the rising costs of clinical research, which are in part due to extensive trial monitoring processes that focus on unimportant details. Risk-based quality management focuses, instead, on "things that really matter". We discuss the role of central statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The chapter "changes to monitoring and auditing" got more than four pages. Although there is no evidence that source data verification alters the results of clinical trials [5][6][7][8], many hours were spent by regulators to find consented solutions for it. The section 'risk assessment' received three quarters of a page.…”
Section: Reasons For the Adverse Impactsmentioning
confidence: 99%
“…The chapter "changes to monitoring and auditing" got more than four pages. Although there is no evidence that source data verification alters the results of clinical trials [5][6][7][8], many hours were spent by regulators to find consented solutions for it. The section 'risk assessment' received three quarters of a page.…”
Section: Reasons For the Adverse Impactsmentioning
confidence: 99%
“…This can be done in many ways: e.g., sharing scanned copies of trial documents via e-mail, sharing computer screen via a video-conferencing application or providing remote access to electronic medical records. A large part of trial costs is attributed to on-site monitoring, which for some large global clinical trials could be up to 60% of all trial costs [ 29 ]. However, there is no evidence to support this approach, and none of the randomised trials comparing intensive with less intensive monitoring have shown clinically relevant treatment outcomes [ 29 ].…”
Section: Monitoring Of Clinical Trialsmentioning
confidence: 99%
“…A large part of trial costs is attributed to on-site monitoring, which for some large global clinical trials could be up to 60% of all trial costs [ 29 ]. However, there is no evidence to support this approach, and none of the randomised trials comparing intensive with less intensive monitoring have shown clinically relevant treatment outcomes [ 29 ]. We strongly advocate an approach of remote monitoring and risk-based monitoring even after the pandemic.…”
Section: Monitoring Of Clinical Trialsmentioning
confidence: 99%
“…A clear distinction between pragmatic and explanatory approaches to clinical trials was proposed nearly fifty years ago, yet most trials conducted today adopt the explanatory approach, which is unnecessarily onerous [ 105 ]. Table 3 provides a comparison of trial characteristics under the explanatory and pragmatic approaches [ 19 ]. The COVID-19 pandemic provided empirical evidence that inefficiencies in clinical research can easily be overcome in pragmatic trials in times of emergency.…”
Section: Clinical Trials For Covid-19 Patientsmentioning
confidence: 99%